Last word : my indictment of the CIA in the murder of JFK - Lane, Mark, active 2007 (Skyhorse Publishing, 2011)
Mark Lane has tried the only case in the history of the United States in which jurors concluded that the CIA killed President Kennedy. While that evidence is clear, there were still pieces missing from the puzzle. How did the CIA control forces of the law on the ground in Dealey Plaza? How did they also control the Dallas Police Department, the Dallas Sheriff's Department, and the United States Secret Service? How did federal authorities prevent the House Select Committee on Assassinations from discovering the truth about the complicity of the CIA? What was the attitude of the United States Secret Service that day in Dallas?